2014
DOI: 10.1287/msom.2013.0453
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Behavior Under Supply Risk:An Experimental Investigation

Abstract: As supply chains become increasingly complex and global in their scale, supplier selection and management in the face of disruption risk has become one of the most challenging tasks for modern managers. Several novel model-based approaches to managing such risks have been developed in the academic literature, but how behavioral tendencies may aect procurement decisions under such conditions has received relatively less attention. In this paper, we present results from a study where paid subjects were asked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 51 publications
3
73
2
Order By: Relevance
“…At the same time, risk aversion also could counteract the effect of bounded rationality when the buyer decides the optimal fixed fee according to project uncertainty (as we observed in the interaction analysis for H1a). Therefore, it is hard to say whether risk aversion triggers or prevents non‐optimal contractual decisions, a finding that is very similar to a previous study on ordering behaviors under supply risk (Gurnani et al, 2013). However, these findings do support the importance of considering risk aversion when explaining non‐optimal decisions.…”
Section: Data Analysis and Resultsmentioning
confidence: 65%
“…At the same time, risk aversion also could counteract the effect of bounded rationality when the buyer decides the optimal fixed fee according to project uncertainty (as we observed in the interaction analysis for H1a). Therefore, it is hard to say whether risk aversion triggers or prevents non‐optimal contractual decisions, a finding that is very similar to a previous study on ordering behaviors under supply risk (Gurnani et al, 2013). However, these findings do support the importance of considering risk aversion when explaining non‐optimal decisions.…”
Section: Data Analysis and Resultsmentioning
confidence: 65%
“…Researchers have also used laboratory studies and field experiments to study the relationship between supplier inventory service level and orders from retailers. Gurnani et al (2013) use laboratory experiments in a multisupplier context to determine how subjects spread orders across two suppliers, one that is perfectly reliable and more expensive, and one that is imperfect and less expensive. In these experiments, subjects increase their orders for the unreliable supplier as that supplier's service level increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We contribute to the nascent field of supply chain risk management, for which Sodhi et al (2012) identified a methodology gap and called for more empirical studies to bridge the gap between theory and practice. Within this field, there is an extensive body of theoretical literature (Tang (2006) provides an excellent review; we also refer readers to Gurnani et al (2014) and Wang et al (2010) and the references therein). The theoretical setting of our paper builds on Wang et al…”
Section: Theoretical and Empirical Literature On Supply Risk Managementmentioning
confidence: 99%
“…Experimental literature on dual sourcing: The closest papers to our work in this domain are Gurnani et al (2014), Goldschmidt et al (2014), and Csermely and Minner (2015). We review the similarities and differences between their work and ours below.…”
Section: Behavioral Operations Managementmentioning
confidence: 99%
See 1 more Smart Citation